1991
DOI: 10.1016/0014-5793(91)80593-r
|View full text |Cite
|
Sign up to set email alerts
|

pH‐dependent changes in structure and RNA‐binding activity of casein kinase 2 from Rana temporaria oocytes

Abstract: It is demonstrated by filter‐binding assay that casein kinase 2 from Rana temporaria oocytes binds rRNA in vitro with high affinity. Ligand‐blotting shows that rRNA‐binding activity is inherent to α and α′ subunits of the enzyme. Increase of pH from 6.5 to 7.5 has little effect on casein kinase but completely suppresses rRNA‐binding activity of the enzyme. Sedimentation coefficient of casein kinase 2 also defends on pH: at pH 7.5 it is mainly 10 S, and at 6.5 – 18 S. At pH 6.95 the amounts of both forms are eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…CK2 is an acidophilic PK, i.e., it preferably phosphorylates substrates with clusters of negatively charged amino acid residues flanking the phosphorylatable serine/threonine residue . Therefore, CK2 is inhibited in a protein substrate competitive manner by polyanions, such as heparin, , negatively charged peptides, and nucleic acids. The inhibitory potency of these compounds is enhanced with increased number of negatively charged residues, reaching low-nanomolar affinity with higher molecular weight homologues. , Recently, we showed that the potency and selectivity of CK2 inhibition can be remarkably increased by the bisubstrate inhibitor approach (reviewed), i.e., construction of conjugates that simultaneously occupy the binding sites of both the phosphodonor nucleotide and phosphoacceptor protein substrate of the PK. Specifically, the bisubstrate inhibitors designed by us (termed ARCs) targeted to CK2, were constructed by conjugation of ATP-competitive inhibitors, such as TBBz or benzoselenadiazole, with oligo- l -aspartate peptides that mimic the protein substrate recognition (consensus) sequence of CK2. , These fragments were joined via a hydrophobic linker derived from octanoic acid (Oca).…”
Section: Introductionmentioning
confidence: 99%
“…CK2 is an acidophilic PK, i.e., it preferably phosphorylates substrates with clusters of negatively charged amino acid residues flanking the phosphorylatable serine/threonine residue . Therefore, CK2 is inhibited in a protein substrate competitive manner by polyanions, such as heparin, , negatively charged peptides, and nucleic acids. The inhibitory potency of these compounds is enhanced with increased number of negatively charged residues, reaching low-nanomolar affinity with higher molecular weight homologues. , Recently, we showed that the potency and selectivity of CK2 inhibition can be remarkably increased by the bisubstrate inhibitor approach (reviewed), i.e., construction of conjugates that simultaneously occupy the binding sites of both the phosphodonor nucleotide and phosphoacceptor protein substrate of the PK. Specifically, the bisubstrate inhibitors designed by us (termed ARCs) targeted to CK2, were constructed by conjugation of ATP-competitive inhibitors, such as TBBz or benzoselenadiazole, with oligo- l -aspartate peptides that mimic the protein substrate recognition (consensus) sequence of CK2. , These fragments were joined via a hydrophobic linker derived from octanoic acid (Oca).…”
Section: Introductionmentioning
confidence: 99%